PERAN GURU DALAM IMPLEMENTASI LITERASI BUDAYA DAN KEWARGAAN DI SMA KEMALA BHAYANGKARI - Aziza, Puja Nur; Zakso, Amrazi; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe title of this research is "the role of the teacher in the implementation of cultural literacy and citizenship in sociology subjects in class x iis 5 sma kemala bhayangkari". The purpose of this research is to determine the role of teachers in the implementation of cultural literacy and citizenship in sociology subjects in class X IIS 5 Kemala Bhayangkari High School, which contains the teacher's role in planning the teacher's role in implementing the teacher's role in evaluating and the teacher's role in motivating. The research method used is descriptive method with qualitative research forms. The data source of this research is sociology teacher and class X students of IIS 5 Kemala Bhayangkari High School. Data collection techniques in this study are through observation, interviews and documentation, while the data collection tools used are observation guides, interview guides and documentation tools. Analysis of the results of the study showed that all forms of teacher role must be related to one another, because the implementation of cultural and citizenship literacy in sociology subjects is strongly influenced by the role of the teacher.Keywords: Implementation, Teacher Role, Literacy